Sensing of pathological tremor using surface electromyography and accelerameter for real-time attenuation - Ferdinan Widjaja (2011)
Tremor is one of the most common movement disorders. Based on Elble and Koller' s definition, it is defined as, "the involuntary rhythmic or semi rhythmic oscillation of a body part resulting from alternating of simultaneous contractions of antagonistic muscle groups". Tremor caused by injuries or diseases such as Parkinson’s disease, stroke, etc., can be problematic both physically and emotionally. If the tremor is affecting the upper limb, the patient will have difficulties even to do activities of daily living such as buttoning, inserting key to keyhole, writing, etc, thus degrading his quality of daily life. Furthermore it may lead to social embarrassment and isolation. The cost of the treatment and the cost borne by the family and community are also significant. This thesis shows the feasibility of real-time tremor attenuation by proposing novel algorithms in an assistive technology solution. The contribution of the proposed system is using surface Electromyography (SEMG) as the sensor to detect the upper limb movement. SEMG is used because it precedes the kinematics data (accelerometer-ACC in this case) by 20-100 ms. This time lead provides the necessary time to process the information and to do real-time compensation of tremor.